Design and Application of Series Flexure Mechanism based on Elliptical Flexure Hinge - Shan Mingcai; Liu Shuang; Kong Xiangjie (Jixie chuandong)
To increase the stroke of precision positioning system,a large stroke series flexure mechanism based on elliptical flexure hinge is presented.The method of pseudo-rigid-body model is applied to analyze the motion process of the series flexure mechanism,and the theoretical model of stiffness and maximum stress is established.Taking the ultrasonic linear motor as the driving element,a unidirectional 2.5 mm stroke as design objectives,the structural parameters of the series flexure mechanism are achieved,the result error between finite element analysis and theoretical calculation is less than 5%,which proved the correctness of the design.A positioning system which having millimeter stroke is built,and a continuous stepping experiment is carried out,the experimental results proved that the system which could realize the precise positioning and has large stroke.